STUDI KELAYAKAN BISNIS PADA USAHA PERTERNAKAN ITIK DI DESA BABATAN PERSPEKTIF EKONOMI ISLAM - rahino, Subekti Fajar Rahino; Evan Setiawan; Eka Sri Wahyuni (Universitas Muhammadiyah Bengkulu, 2025)
The purpose of this study is to examine the feasibility of duck farming in Babatan village based on the perspective of sharia economics. This kind of research is field research. That is, direct observation of the object being studied to obtain relevant data and interpret the object according to what it is. The results of the study show that there is a feasibility study of the duck farming business in Babatan Village, this business is feasible to be developed from six aspects of feasibility. However, from the Islamic economic side, there are still shortcomings in the application of social values, especially related to environmental impacts such as annoying odors. Therefore, this business can be continued with a record of improvement to achieve mutual benefit according to the principles of sharia economics